Renal Tumors in Pregnancy: A Case Report Focusing on the Timing of the Surgery and Patient Positioning - Hamidreza Ghorbani; Mahdi Mottaghi; Salman Soltani (Case Reports in Obstetrics and Gynecology)
Management of renal mass during pregnancy is challenging. There is no consensus regarding the fundamental timing issues (which trimester) of the interventions and patient positioning during the procedures. We present three pregnant women with renal mass and their management, focusing on patient positioning and timing of surgical intervention. All patients were positioned supine with a 30-degree rotation to the left lateral without signs of compromising fetal circulation. This report’s three major takeaway points are the following: (1) Renal mass biopsy might be more beneficial in pregnant women than the normal population (unless CT findings suggest vascular angiomyolipomas) to achieve a definite diagnosis and avoid unnecessary interventions during pregnancy. (2) Surgical interventions, if indicated, should be performed as soon as possible and are applicable in all trimesters of pregnancy. (3) A minimum of 15-degree left lateral tilt (for both right- and left-sided renal masses) can provide enough venous return during the nephrectomy.